# Integration of Trigonometric Function

We at ask-math believe that educational material should be free for everyone. Please use the content of this website for in-depth understanding of the concepts. Additionally, we have created and posted videos on our youtube.

We also offer One to One / Group Tutoring sessions / Homework help for Mathematics from Grade 4th to 12th for algebra, geometry, trigonometry, pre-calculus, and calculus for US, UK, Europe, South east Asia and UAE students.

Affiliations with Schools & Educational institutions are also welcome.

Please reach out to us on [email protected] / Whatsapp +919998367796 / Skype id: anitagovilkar.abhijit

We will be happy to post videos as per your requirements also. Do write to us.

In this section we will discuss the integration of trigonometric function.
Recall the definitions of the trigonometric functions and trigonometric identities.
1) $tan(x) = \frac{sin(x)}{Cos(x)}$

2) $cot(x) = \frac{cos(x)}{sin(x)}$

3) $sec(x) = \frac{sin(x)}{Cos(x)}$

4) $csc(x) = \frac{1}{sin(x)}$

5) $sin^{2}(x) + cos^{2}(x)=1$

6) $1 + tan^{2}(x)=sec^{2}(x)$

7) $1 + cot^{2}(x)=csc^{2}(x)$

8) sin(2x) = 2 sin(x) cos(x)

9) cos(2x) = $2cos^{2}(x) - 1 \Rightarrow cos^{2}(x)=\frac{1 + cos(2x)}{2}$

10) cos(2x) = $1-2sin^{2}(x) - 1 \Rightarrow sin^{2}(x)=\frac{1 - cos(2x)}{2}$

11) cos(2x) = $cos^{2}(x) - sin^{2}(x)$

You have already learnt the derivatives of trigonometric functions. Integration is anti-differentiation.

1) $\frac{\text{d}}{\text{d}x}sin(x) = cos(x) \Rightarrow \int_{}^{}cos(x)dx = sin(x) + c$

2) $\frac{\text{d}}{\text{d}x}cos(x) = -sin(x) \Rightarrow \int_{}^{}sin(x)dx = -cos(x) + c$

3) $\frac{\text{d}}{\text{d}x}tan(x) = sec^{2}(x) \Rightarrow \int_{}^{}sec^{2}(x)dx = tan(x) + c$

4) $\frac{\text{d}}{\text{d}x}cot(x) = -csc^{2}(x) \Rightarrow \int_{}^{}csc^{2}(x)dx = -cot(x) + c$

5) $\frac{\text{d}}{\text{d}x}sec(x) = sec(x)tan(x) \Rightarrow \int_{}^{}sec(x)tan(x)dx = sec(x) + c$

6) $\frac{\text{d}}{\text{d}x}csc(x) = -csc(x)cot(x) \Rightarrow \int_{}^{}csc(x)cot(x)dx = -csc(x) + c$

## Examples on Integration of Trigonometric Function

Example 1 : Integrate 2sin(x) with respect to x.

Solution : $\int_{}^{}2sin(x)dx$

= 2$\int_{}^{}sin(x)dx$

= -2cos(x)

$\int_{}^{}2sin(x)dx$= -2cos(x) + c

Example 2 : Integrate $\frac{1}{2}sec^{2}(x)$ with respect to x.

Solution : $\int_{}^{}\frac{1}{2}sec^{2}(x)dx$

=$\frac{1}{2} \int_{}^{}sec^{2}(x)dx$

=$\frac{1}{2} tan(x)$

$\int_{}^{}\frac{1}{2}sec^{2}(x)dx = \frac{1}{2} tan(x) + c$

Example 3 : Integrate $\frac{2}{1+cos(2x)}$ with respect to x.

Solution : $\int_{}^{}\frac{2}{1+cos(2x)}dx$

=$\int_{}^{}\frac{2}{2cos^{2}(x)}dx$ ( Using the trigonometric identity)

=$\int_{}^{}sec^{2}(x)dx$

= tan(x)

$\int_{}^{}\frac{2}{1+cos(2x)}dx = tan(x) + c$

Example 4: Integrate $\frac{cos(2x) + 2sin^{2}(x)}{cos^{2}(x)}$ with respect to x.

Solution : $\int_{}^{}\frac{cos(2x) + 2sin^{2}(x)}{cos^{2}(x)}dx$

=$\int_{}^{}\frac{1-2sin^{2}(x) + 2sin^{2}(x)}{cos^{2}(x)}dx$ ( Using the trigonometric identity)

=$\int_{}^{}\frac{1}{cos^{2}(x)}dx$

=$\int_{}^{}sec^{2}(x)dx$

= tan(x)

$\int_{}^{}\frac{cos(2x) + 2sin^{2}(x)}{cos^{2}(x)}dx = tan(x) + c$

Example 5 : Integrate $(x^{2}+4sin(x))$ with respect to x.

Solution : $\int_{}^{}(x^{2}+4sin(x))dx$

= $\int_{}^{}x^{2}dx + \int_{}^{}4sin(x)dx$

= $\int_{}^{}x^{2}dx + 4\int_{}^{}sin(x)dx$

= $\frac{x^{(2+1)}}{2+1} - 4cos(x)$ (using the power rule of integration)

= $\frac{x^{3}}{3} - 4cos(x)$

$\int_{}^{}(x^{2}+4sin(x)dx = \frac{x^{3}}{3} - 4cos(x) + c$